Analisis Lokasi Rawan Banjir Daerah Aliran Sungai Landak Menggunakan Analytic Hierarchy Process - Ruri Restu Ramadandi; Stefanus Barlian Soeryamassoeka; Danang Gunarto Ramadandi (PT. Inovasi Teknologi Komputer, 2026)
Flooding is a common natural disaster that has negative impacts on both people and the environment. One of the regions in Indonesia frequently affected by flooding is the Landak River Basin (DAS). Flooding in this area is believed to be caused by land conversion to oil palm plantations, sedimentation leading to river siltation, and the river's meandering nature. This study employed the Analytic Hierarchy Process (AHP) to identify the region’s vulnerability levels. Based on the results of the Focus Group Discussion (FGD), the criteria used included flood duration, flood depth, topographic conditions, rainfall, and tidal fluctuations, with the assessment covering all sub-districts within the Landak River Basin. The analysis results indicate that Kuala Mandor/B Subdistrict has the highest vulnerability level (20.04%), followed by Sungai Ambawang Subdistrict (19.09%) and Sebangki Subdistrict (10.81%). Meanwhile, Air Besar Subdistrict has the lowest vulnerability level (3.23%). This study concludes that comprehensive, integrated spatial and regional planning from upstream to downstream is essential to mitigate the impacts of flooding in the Landak River Basin.